Inv dup (15): Is the electroclinical phenotype helpful for this challenging clinical diagnosis? - Valente, K. D.; Freitas, A.; Fridman, C.; Varela, M.; Silva, A. E.; Fett, A. C.; Koiffmann, C. P. (Elsevier B.V., 2006)
Objective: To study the electroclinical phenotype in 5 patients with large Supernumerary marker chromosome referred as inv dup (15), in an attempt to analyze the electroclinical spectrum in order to determine if the binomial epilepsy-EEG is stereotyped enough to corroborate this challenging diagnosis.Methods: Five patients with large inv dup (15) were submitted to EEG and/or V-EEG, with a minimum duration of 2 h. Two certified neurophysiologists analyzed all EEG tracings simultaneously, blinded to clinical and molecular data. Epilepsy was characterized by detailed history and a standard questionnaire according to International League Against Epilepsy guidelines and corroborated by V-EEG findings.Results: Epilepsy started during infancy in 4 patients, in 3 with spasms. Spasms were easily controlled in one but not in others. Epilepsy evolved with generalized seizures in two patients and, generalized and focal in one. Currently, 3 patients present refractory epilepsy and two are seizure-free. In one patient, only one isolated episode suggestive of a secondary generalized tonic-clonic event occurred at the age of 12 years without recurrence. Regarding the EEG, patients had distinct features, except for two patients with very high amplitude fast activity, resembling recruiting rhythm. Despite good seizure outcome in 3 patients, EEGs remained remarkably abnormal with frequent epileptiform discharges over poorly organized background.Conclusions: Our data showed a heterogeneous electroclinical phenotype with generalized and partial epilepsy, presenting distinct degrees of severity and refractoriness.Significance: Our findings suggest that it is not possible to delineate an electroclinical phenotype in this neurogenetic syndrome. Therefore, inv dup (15) remains as a diagnostic challenge and epilepsy and EEG features are valuable only when inserted in the proper clinical context. (c) 2006 International Federation of Clinical Neurophysiology. Published by Elsevier B.V.. All rights reserved.
Keywords: Chromosome; epilepsy; EEG; inv dup (15); genotype